Development economics through the decades a critical look at 30 years of the world development report - Yusuf, Shahid (Washington, D.C. World Bank, 2009)
Since 1978, the World Bank's annual 'World Development Report' (WDR) has provided in-depth analysis and policy recommendations on a specific and important aspect of international development from agriculture, the role of the state, economic growth, and labor to infrastructure, health, the environment, and poverty. In the process, it has become a highly influential publication that is consulted by international organizations, national governments, scholars, and civil society networks to inform their decision-making processes. In this essay, Shahid Yusuf examines the last 30 years of development economics, viewed through the WDRs. The essay begins with a brief background on the circumstances of newly independent developing countries and summarizes some of the main strands of the emerging field of development economics. It then provides a sweeping examination of the coverage of the WDRs, reflecting on the key development themes synthesized by these reports and assessing how the research they present has contributed to policy making and development thought. The book then looks ahead and points to some of the big challenges that the World Bank may explore through future WDRs. The essay is followed by five commentaries, each written by a distinguished economist or development practitioner, which further explore this terrain from different perspectives. Together, the contents of this volume provide an extraordinary and remarkably compact tour of development economics through, around, and beyond the WDR. It will be invaluable to anyone interested in the evolution of development economics over the past three decades as well as for students, scholars, and policy makers in the field of development. To commemorate the 30th anniversary of the 'World Development Report', this book is being simultaneously published with 'The Complete World Development Report, 1978?2009'. This DVD is a fully-searchabel digital archive that contains the full collection of WDRs. For more information about the DVD or the 'World Development Report', visit www.worldbank.org/wdr.
Includes bibliographical references (p. 157-182) and index.
Keywords: Development economics